Bacterial Isolation Which is Potential as Cellulosa Pedegradation in Coastal Performance In Tanjungpinang City - Iwan Iskandar; Hevi Horiza (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
Many black water or feces and urine field observations in Tanjung Pinang City were dumped directly into the ditches, rivers, and sea. This proves that the management of domestic liquid waste in the City of Tanjungpinang, especially black water, has not yet received serious attention, resulting in a decline in environmental quality. One of the stages in processing black water is decomposition. The decomposition process can be assisted by bacteria, one of which is cellulose-degrading bacteria. This study aims to find bacterial isolates that have the potential to degrade cellulose in feces from coastal soils in Tanjung Pinang City. This research is a laboratory experimental research. The results of this study were obtained 16 bacterial isolates that can degrade cellulose. From these 16 isolates, 3 genera of bacteria were obtained, namely Pseudomonas, Acetobacter and Acinetobacter. Keywords: Cellulose Degradation Bacteria, Coastal Soil